EVALUASI KETERSEDIAAN KOLEKSI ANAK DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KUBU RAYA - Indah Sari; Sahidi Sahidi (Universitas Tanjungpura, 2020)
AbstractThe study was to evaluate the availability of children's collections in the archive service library and the regional library. The method used was a qualitative research method. The thing to do in providing a collection of children was to make a selection, which in turn makes a collection. Selecting a collection of children was tailored to the library's environment in making a collection of children using two ways to make it possible without a time limit, depending on the user's need to do it by purchasing the book store. Studies sbeowed that the library's library's collection of 80 books with 309 copies that are still fairly low in the 2019 child collection, so library authorities are required to supplement the child's collection of information and address the needs of the neighborhood user to a high degree of 2019 child collections.Keywords: evaluation, availability of collection, child collection